Active Fault Zones of The 2006 Yogyakarta Earthquake Inferred from Tilt Derivative Analysis of Gravity Anomalies - Lina Handayani (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2019)
The 2006 Yogyakarta Earthquake had caused a disaster in Bantul area. Several institutions had reported different results for the epicenter location. However, aftershocks studies indicated that the rupture area was at about 10 km east of Opak Fault. Analysis of gravity anomaly, including several degrees of residual anomalies and tilt derivative, facilitated this regional tectonic study to determine the structural constraints on the main earthquake and its aftershocks. The Yogyakarta area was primarily characterized by several SW-NE faults; one of them is the Opak Fault. Among those faults,, there are a series of WNW-ESE faults. Several groups of these lineations indicated a presence of some pairs of parallel strike-slips faults that formed pull-a-part basins. The obtained structural pattern has signified the dynamic response of the force from the subduction of the Australian Plate toward Sunda (Eurasia) Plate.  The subduction force produced the strike-slip fault in a parallel direction of subduction, and subsequently, the faults caused the formation of thrust structures that are perpendicular to them.Gempabumi Yogyakarta pada tahun 2006 telah menyebabkan bencana di daerah Bantul dan sekitarnya. Lokasi episenter yang ditentukan oleh beberapa lembaga menunjukkan hasil yang berbeda. Tetapi analisa gempabumi susulan telah menunjukkan daerah pegerakan hingga 10 km ke sebelah timur dari Sesar Opak. Analisa anomali gayaberat yang terdiri dari perhitungan anomali sisa dan turunan kemiringan (tilt derivative) diharapkan dapat membantu studi tektonik regional dalam menentukan batasan struktur yang menyebabkan kejadian gempabumi di daerah Yogyakarta. Daerah ini dicirikan oleh sesar-sesar berarah BD (Barat daya)-TL (Timur laut), yang salah satunya adalah Sesar Opak. Di antara sesar-sesar tersebut, terdapat pula deretan sesar-sesar berarah BBL (Barat barat laut)-TTG (Timur tenggara). Beberapa kelompok kelurusan-kelurusan membentuk kemungkinan adanya cekungan pull-a-part, yang terbentuk karena adanya deretan sesar-sesar strike-slip. Pola struktur yang diperoleh menunjukkan respon dinamik dari subduksi Lempeng Australia terhadap Lempeng Eurasia (Sunda). Tekanan dari gaya subduksi menyebabkan terbentuknya sesar-sesar strike-slip. Kemudian sesar-sesar tersebut menyebabkan adanya struktur sesar naik yang tegak lurus terhadapnya.